Romantic Liars - Lee, D. author. aut Link
XIV, 249 p.
Keywords: Lee unfolds the stories of six women with a cast of supporting characters such as Samuel Taylor Coleridge, Benjamin Franklin, Stamford Raffles and Napoleon against the grand narrative of England's 18th century empire building. This book is a meticulously researched, spellbinding tale of tragedy, transformation and triumph in the age of reason.